Effect of oxidation and geometrical dimensions of carbon nanotubes on Hg(II) sorption and preconcentration from real waters - El-Sheikh, Amjad H.; Al-Degs, Yahya S.; Al-As'ad, Randa M.; Sweileh, Jamal A. (Desalination, 2011)
This study reports for the first time the use of oxidized and non-oxidized multi-walled carbon nanotubes (MWCNTs) of different geometrical dimensions for Hg(II) adsorption and preconcentration in water samples. The shapes of the Hg isotherms varied from L2, C1 and H2 according to the dimensions and oxidation conditions of the MWCNTs. Analysis of adsorption data by Langmuir, Freundlich and Dubinin–Radushkevich isotherms revealed that Hg(II) removal by L-MWCNT-4060-NA (nitric acid-oxidized MWCNT of external diameter 40–60 nm and length 5–15 μm) has the lowest sorption energy, which reflects the favorable uptake of Hg(II) by this adsorbent. Sorbents showed variable sorption capacities for mercury (0.70–3.83 mg g −1). However, in the preconcentration experiments, L-MWCNT-4060-NA exhibited the highest enrichment efficiency for a preconcentration of 100 μg L −1 Hg(II) at pH 7. The limit of quantifications of Hg(II) was 0.0123 μg L −1 in water. Analysis of Hg(II) in tap and reservoir waters gave high spike recovery (88–95%, RSD < 3%). Mineral water was used to check interference from foreign ions. The method was validated by determination of mercury in digested phosphate rock samples and certified reference Polish tobacco leaves, in which the method was highly accurate and precise. ► Oxidation and dimensions of MWCNT affect Hg sorption. ► Various sorption models are applied. ► Solid phase extraction procedure of Hg(II) is optimized. ► The method is precise and accurate. ► Hg was determined in real waters, tobacco and phosphate rock.